STUDI VALIDASI SEMI-QUANTITATIF FOOD FREQUENCY QUESTIONNAIRE (FFQ) DAN RECALL 1 X 24 JAM TERHADAP ASUPAN ZAT GIZI MAKRO IBU HAMIL - Yellyta Ulsafitri; Media Fitri (Universitas Fort De Kock, 2023)
Nationally, 44.8% of pregnant women consume energy below the minimum requirement of less than 70%. Dietary surveys or food consumption assessments are one of the methods used in determining the nutritional status of individuals or groups. The use of the FFQ helps monitor nutritional status which aims to improve the health of mothers and newborns. This aims to develop a semi-quantitative food frequency questionnaire method on macronutrients for pregnant women and as a reference standard, the 24-hour food recall method was used at the Bukittinggi City Health Center. This type of research is an analytic survey study with a cross-sectional design to see differences and correlations in the amount of intake of macronutrients using a semi-quantitative food frequency questionnaire method with 24-hour food recall. The population in this study were pregnant women in the second and third trimesters of pregnancy who went to the puskesmas in Bukittinggi. The results of measuring the average intake of macronutrients produced by the semi-quantitative food frequency questionnaire method were higher than the 24-hour food recall method. The highest correlation value was in energy (r=0.564> 0.3 ) and the smallest was in protein (r=0.226 <0.3). From the correlation results, it was found that the Semi-Quantitative Food Frequency Questionnaire method is a valid tool for measuring energy, fat and carbohydrate intake in pregnant women at the Bukittinggi City Health Center.